JS-NG-3: UNIQUE IMAGING FINDINGS IN RENAL ARTERY FIBROMUSCULAR DYSPLASIA. (January 2023) - Kang, Yuanyuan; Xu, Jianzhong; Wang, Jiguang
Abstract : A 35-year-old female patient with fluctuating blood pressure was referred to hypertension department for investigation of possible secondary hypertension. Computed tomographic angiography (CTA) of the renal arteries was performed, demonstrating abnormal right renal artery at the medial portion of the vessel with complete tubular narrowing and right kidney atrophy (right 79*35 mm, left 109*45 mm) (Panel A). Subsequent renal arteriography confirmed the long tubular narrowed right renal artery (Panel C) and the established severe tortuosity collateral vessel from the abdominal aorta (Panel B). The etiological diagnosis of the renal artery stenosis in this young woman was challenging and was supposed to be congenital renal dysplasia. Catheter-based angioplasty was not recommended. However, intravascular ultrasound (IVUS) revealed that it was not congenital narrowed artery, but concentric intimal-medial thickening caused stenosis of the vessel (Panel E). Therefore, renal artery fibromuscular dysplasia (FMD) was diagnosed and considered to be intimal type. Balloon angioplasty was performed, and IVUS showed that the lesion lumen was dilated successfully (Panel F). However, a bailout stent had to be placed because of intimal dissection during angioplasty, and renal blood flow was restored after procedure (Panel D). One month after the procedure, the patient was normotensive without any antihypertensive medication. At 1 year follow-up, the 99m Tc-glomerular filtration rate of the right kidney increased from 19.7 to 40.4 ml/min. FMD is a nonatherosclerotic, noninflammatory vascular disease that most commonly affects renal arteries and is recommended to be classified according to angiographic finding as multifocal FMD or focal FMD. Compared with multifocal FMD, focal FMD is less often seen, and the diagnosis of some cases is challenging. In the present case, such a long tubular stenosis of renal artery is rare, and the diagnosis was confirmed by IVUS. IVUS may be a useful tool for the diagnosis of focal FMD.